The Mediation Role of Organizational Support on The Influence of Work-Life Balance on Generation Z Employees' Commitment in 3-Star Hotels in Pontianak - Meilani Putri Maharani; Deasy Rinayanti Pelealu (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this research is to look at how Generation Z workers at 3-star hotels in Pontianak City feel about their work-life balance and how it affects their commitment to the company. A new generation of workers, Generation Z (those born between 1997 and 2012), has high expectations for a healthy work-life balance and places a premium on this concept, which in turn affects how loyal they are to their employers (Twenge, 2020). A quantitative methodology based on survey research was employed in this study. The sample was selected at random from among Generation Z workers at multiple 3-star hotels in Pontianak. A survey measuring organizational support, employee commitment, and work-life balance was used to collect data. The mediation hypothesis was tested using path analysis. The results show that work-life balance has a favorable and substantial effect on employee dedication. In addition, research has shown that organizational support has a favorable and substantial effect on employee commitment. The main takeaway from this research is that there is a mediation role for organizational support in the relationship between work-life balance and employee commitment. This indicates that the positive impact of work-life balance on the levels of commitment among Generation Z employees is amplified when they believe their employer supports them, meaning that they are recognized for their efforts and their well-being is prioritized (Eisenberger et al., 1986). This study highlights the importance of hotel management prioritizing work-life balance and creating a supportive work environment for Generation Z employees. This will help them stay committed and engaged in the competitive hospitality business.